Automatización residencial un desafío profesional para el monitoreo de personas en condición de discapacidad visual (2020)
People with visual impairment have a permanent condition such as low vision or no perception of light, making it difficult for them to perform daily activities in their home and outside. The World Health Organization estimates that there are about 36 million people with this condition in Colombia, 406,193 by 2014. In Tunja the population with disabilities is 2914, there are people with permanent alteration in eyes 44.5%, a population that is difficult to develop daily activities, from the most basic such as moving around their living environment, to the most complex in the handling of appliances. Under these considerations, electronic engineering and health professions join their knowledge to generate tools that help this type of population. The design and implementation of a prototype of a home automation control and monitoring system, through IoT using voice commands, is a technological strategy of direct implementation, with the use of the second generation Intel Galilean card, opens an opportunity in the use of a programming device with the benefits to develop home automation control through voice commands. The programming interface on the card includes Arduino's IDE, with an App inventor application, the recognition of the commands sent to the Intel processing board, through a cell phone with Android operating system, likewise allows monitoring of variables such as temperature and heart rate. To give more amplitude to the Project, the health area staff guides the development of the interface with the Ubidots platform, in such a way that it is clear and timely to generate readings about the patient's condition during the monitoring time.